Optimalisasi Produktivitas Keterlambatan MEP (Mechanichal Elektrikal Plumbing) Gedung F Poliklinik Terpadu RSUD Prof Dr Soekandar Mojosari Kabupaten Mojokerto Melalui Metode Earned Value - Irawan, Irawan; Thesisa, Cilda (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
This study aims to optimize the productivity of MEP (Mechanical, Electrical, Plumbing) work on the Integrated Polyclinic Building F construction project at Prof. Dr. Soekandar Mojosari Hospital, Mojokerto Regency using the Earned Value (EV) method. The main problems that often occur in construction projects are delays in completion time and cost overruns that can result in decreased productivity. The Earned Value method is used as a management tool to quantitatively measure project performance and provide more accurate information about project progress and deviations from the planned schedule and budget. This research analyzes project performance data through three main variables: Planned Value, Earned Value, and Actual Cost. The analysis showed that there were several errors that caused the project to be delayed and over budget. Using performance indicators such as Schedule Performance Index and Cost Performance Index, this study found important areas that need improvement and recommended optimization strategies to improve the efficiency and effectiveness of MEP works. It is expected that the implementation of these strategies will minimize delays and control costs, so that project objectives can be achieved within the set time and budget.